Direct Integration of Numerous Dams and Reservoirs Outflow in Continental Scale Hydrologic Modeling. Issue 9 (15th September 2021) - Tavakoly, Ahmad A.; Gutenson, Joseph L.; Lewis, James W.; Follum, Michael L.; Rajib, Adnan; LaHatte, William Clay; Hamilton, Chase O.
Abstract: Despite the recent developments in continental‐scale streamflow and flood inundation modeling frameworks, effects of time‐specific and spatially explicit storage‐release dynamics of numerous dams and reservoirs remain underexplored. This paper fills this knowledge gap by directly inserting operational daily flow release data at 175 dam locations into a streamflow simulation of ∼1.2 million river reaches in the Mississippi River Basin (MRB), and therefore quantifying the effect of these regulations on streamflow and flood inundation extents. Using a streamflow routing model called the Routing Application for Parallel computatIon of Discharge (RAPID) and flood inundation mapping model called AutoRoute, two simulation scenarios were constructed respectively including and excluding the daily flow releases from those dams and reservoirs for a 10‐year period (2005–2014). Flood inundation maps were simulated for peak flow conditions at a ∼10‐m hyper spatial resolution. Kling‐Gupta efficiency (KGE) values show that streamflow model performance considerably improved when reservoirs were included in the modeled system, varying from 2% in the eastern region to 380% in the drier western region. Despite small variation of streamflow model improvement with reservoir release inclusion in the eastern region of the basin, the flow model was able to better capture observed peak flows. For a 1% change in streamflow, we observe a 0.8% change in estimated flood inundation. Comparisons to three observed flood events in the MRB demonstrate that the flood inundation estimates improve when percent change in streamflow is relatively high. Overall, inclusion of reservoir release resulted in substantial improvement in continental‐scale streamflow and flood inundation mapping. Plain Language Summary: Dams and reservoirs are important structures that alter the flow of rivers to provide important services such as flood reduction, hydropower generation, and water storage for irrigation and recreation. We can use computer modeling to simulate the flow of rivers and the operation of dams. Most of the time, researchers approximate the operation of dams using various assumptions. However, we do not fully understand how much the real‐life operation of reservoirs impacts river flow across large spatial extents and by products, such as flood extent. In this study, we combine observed dam releases and computer modeling to replicate river flow in a large river system with many dams. We show how the influence of dams on water movement impacts our modeling of flood maps. Our results reveal that despite the common judgment, small reservoirs can have large influence on water movement. We also show that the dams, to varied degrees, have considerable impact on flood maps when the dams significantly affect the flow of rivers. Key Points: Inclusion of numerous reservoir outflows improves continental‐scale streamflow and hyper‐resolution flood inundation mapping Relative changes to peak flow simulation are substantial downstream of many smaller dams Results show how reservoir effects on streamflow propagate from upstream to downstream